U-Shape Nonlinearity of Ownership Concentration on Firm Value - Pratama, Ahmad Aziz Putra (UNIVERSITAS NEGERI SURABAYA, 2019)
The ownership and value relationship of the company has a lot of contentious issues. Previous studies have only examined the linear effect of ownership concentration on company value. In contrast to previous studies, the novelty of this study is to test the effect of nonlinearity in the concentration of ownership on company value using 240 non-financial companies listed on the Indonesia Stock Exchange during the period 2010-2018 with 2,151 observations. The results showed that the concentration of ownership showed the effect of nonlinear U-shaped on firm value. This study confirms that ownership concentration negatively influences the firm's value first and will show a positive effect after reaching a certain point. In addition, the debt level and firm size have a positive effect on firms value.